PENANGANAN DAN PERLINDUNGAN HUKUM TERHADAP ORANG DALAM GANGGUAN JIWA (ODGJ) OLEH PEMERINTAH DAERAH DI KAB.BULUKUMBA PERSPEKTIF SIYASAH SYAR’IYYAH - Subhan,; Basri, Halimah (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2024)
The purpose of this study was to determine the handling and legal protection by the regional government of Bulukumba district for people with mental disorders (ODGJ). The results of this study are that the treatment carried out by the regional government of Bulukumba Regency for people with mental disorders (ODGJ) has gone well, namely doing homecare, checking identity and car facilities for treatment. The legal protection provided by the regional government of Bulukumba Regency does not yet have specific rules regarding people with mental disorders (ODGJ), but it is included in Regional Regulation No. 2 of 2018 concerning protection and services for persons with disabilities. In the siyasah syar'iyyah perspective, the regional government of Bulukumba district has carried out its responsibilities based on Q.S an-Nisa/4:58 and 59, also based on several hadiths, such as providing social rehabilitation facilities and infrastructure for people with mental disorders.